When standards have better distributional consequences than carbon taxes - Jiaxin Zhao; Linus Mattauch (ZBW - Leibniz Information Centre for Economics, 2021)
Carbon pricing is the efficient instrument to reduce emissions. However, the geographical and sectoral coverage of substantial carbon pricing is low, often due to concerns that pricing may increase economic inequality. Regulatory standards such as fuel economy standards are more popular. But do they have an equity advantage over carbon pricing? We develop two new formal models to identify economic situations, in which standards could be preferred over carbon pricing. First, we prove that an efficiency standard can be more equitable than carbon pricing when consumers exhibit a preference for high-carbon technology attributes. Evidence from the US vehicle market confirms this finding. Second, we show theoretically, and by means of a numerical application to the Chinese transport sector, that intensity standards are preferable when richer households consume more goods with higher carbon intensity. Our results hold when the revenue from carbon pricing is not very progressively redistributed. These insights can help advance decarbonisation when pricing remains unpopular.
Keywords: H22; H23; Q52; Q54; 330; Incidence; Distributional effects; Carbon pricing; Efficiency standards; Intensity standards